2014
DOI: 10.1111/his.12353
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic lobular carcinoma in situ of the breast: clinicopathological review of 47 cases

Abstract: Background Pleomorphic lobular carcinoma in situ (PLCIS) of the breast is a distinctive entity, and yet its behavior and management are unclear. The purpose of this study was to review a relatively large number of cases and to evaluate the risk of recurrence. Methods Cases of PLCIS (n=47) over a 12 year-period were reviewed. The clinical, radiologic and pathologic findings were recorded. Immunohistochemistry for estrogen receptor (ER), progesterone receptor (PR) and HER2 were performed. Results Thirty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
5
36
2
1
Order By: Relevance
“…The cells were considered large (grade III nuclei) when their size was at least four times larger than that of a mature lymphocyte. 19 Concurrent lesions that normally warrant surgical intervention were also recorded including flat epithelial atypia, ADH, papilloma, and radial scar.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were considered large (grade III nuclei) when their size was at least four times larger than that of a mature lymphocyte. 19 Concurrent lesions that normally warrant surgical intervention were also recorded including flat epithelial atypia, ADH, papilloma, and radial scar.…”
Section: Methodsmentioning
confidence: 99%
“…As observed above, the numbers of patients in these studies are not sufficient to lead to any solid conclusions. However, Downs-Kelley et al (26) and Khoury et al (27) and indicated that radiotherapy led to a lower recurrence rate in their case series. Furthermore, Khoury et al (27) noted that patients on hormone therapy contributed to half of the recurrence cases.…”
Section: The Effect Of Surgical Margins and Adjuvant Therapy On Recurmentioning
confidence: 90%
“…However, Downs-Kelley et al (26) and Khoury et al (27) and indicated that radiotherapy led to a lower recurrence rate in their case series. Furthermore, Khoury et al (27) noted that patients on hormone therapy contributed to half of the recurrence cases. This issue may need to be explored in larger well-designed prospective studies.…”
Section: The Effect Of Surgical Margins and Adjuvant Therapy On Recurmentioning
confidence: 90%
See 2 more Smart Citations